Cell invasion and strain dependent induction of suppressor of cytokine signaling-1 by Toxoplasma gondii - Stutz, Andrea; Keßler, Henning; Meissner, Markus; Dalpke, Alexander (Immunobiology, 2012)
Toxoplasma gondii is an intracellular parasite that has to cope with the microbicidal actions of IFNγ. Previously we reported that parasite-mediated induction of suppressor of cytokine signaling protein 1 (SOCS1) contributes to inhibition of IFNγ signaling. However, the signaling requirements remained elusive. We now show that induction of SOCS1 and inhibition of nitric oxide production by IFNγ was independent of stimulation of Toll-like receptors. Instead, infection by T. gondii resulted in induction of egr transcription factors which have been reported to regulate SOCS expression. Indeed, induction of egr2 as well as SOCS1 was dependent on p38 MAP kinase and blockade of egr inhibited SOCS1 expression. Moreover, we found that Mic8, a previously identified invasion factor of T. gondii, was necessary for SOCS1 regulation and escape of IFNγ mediated nitric oxide secretion within macrophages. Surprisingly, when further analyzing Mic8 deficient parasites we noted that inhibition of IFNγ mediated up-regulation of MHC-class II and ICAM1 molecules was independent of cell invasion. Furthermore, these inhibitory effects were equally observed in type I and II strains of T. gondii and were dependent on excreted and secreted antigens. In contrast, only the virulent RH type I strain additionally induced SOCS1 and efficiently inhibited nitric oxide secretion by IFNγ. The results show that T. gondii makes use of two different mechanisms to escape from IFNγ activity with one mode being strain dependent and relying on active cell invasion and SOCS1 induction.